Gender Equality and Maternal Burnout: A 40-Country Study. (February 2022) - Roskam, Isabelle; Gallée, Laura; Aguiar, Joyce; Akgun, Ege; Arena, Andrew; Arikan, Gizem; Aunola, Kaisa; Bader, Michel; Barham, Elizabeth J.; Besson, Eliane; Beyers, Wim; Boujut, Emilie; et al.
In Western countries, recent decades have witnessed a revolution toward gender equality. Inequalities have been greatly reduced in areas such as education or employment. Because inequalities lead to distress, this development has largely benefited women. One notable exception is the realm of parenting, which has remained rife with inequalities even in the most egalitarian countries. We hypothesized that experiencing inequality in parenting when one holds egalitarian values and raising a child in a country characterized by a high level of gender equality in other areas, increases mothers' psychological distress in the specific area of parenting. Multilevel modeling analyses computed among 11, 538 mothers from 40 countries confirmed this prediction: high egalitarian values at the individual level and high gender equality at the societal level are associated with higher burnout levels in mothers. The associations hold beyond differences in sociodemographic characteristics at the individual level and beyond economic disparities at the societal level. These findings show the importance of egalitarian values and gender equality and their paradoxical effect when inequalities are still present in specific areas as parenting. This study reveals the crucial need to act not only at the micro level but also at the macro level to promote gender equality in parenting and prevent parental burnout.